The evolution of Argentine´s military intelligence policy: ruptures and continuities (1990-2015) - Poczynok, Iván (2017)
This article analyzes the political factors that crossed the definition of Argentine´s military intelligence policy between 1990 and 2015. The argument is that this activity was conditioned by two assumptions widely held by the governments of this period: that military intelligence is dangerous for democratic stability; and that Argentina does not have external problems that may require this type of knowledge in the medium term. These elements not only made “unnecessary” the definition of an intelligence policy -from the perspective of the local elites- but also shaped a status quo that maintained the subordination of the country's defense interests to foreign strategic perceptions.